Age and sex differences in body composition among Indonesian adults: a cross-sectional study - Evelin Malinti; Yunus Elon; Imanuel Sri Mei Wulandari (Poltekkes Kemenkes Bandung, 2026)
Background: Differences in body composition across adulthood are associated with increased metabolic risk and functional decline. Although body mass index (BMI) is widely used to assess nutritional status, it has limitations in distinguishing adiposity from skeletal muscle mass. Objective: This study aimed to analyze differences in body composition according to age and sex, and to examine the associations between age and BMI, total body fat, visceral fat, and skeletal muscle mass among Indonesian adults. Methods: A cross-sectional study was conducted among 282 adults aged ≥18 years using purposive sampling. Body composition was assessed using bioelectrical impedance analysis. Statistical analyses included Spearman’s rho correlation, Kruskal–Wallis test, and ordinal logistic regression. Results: A total of 51.1% of participants were classified as obese, while 77.3% exhibited low skeletal muscle mass. Age was positively correlated with total body fat (ρ = 0.259; p < 0.001) and visceral fat (ρ = 0.267; p < 0.001), and negatively correlated with skeletal muscle mass (ρ = −0.294; p < 0.001). Middle-aged adults demonstrated the highest adiposity levels, whereas younger adults exhibited higher skeletal muscle mass. Conclusion: Older age was associated with increased adiposity and reduced skeletal muscle mass. Comprehensive body composition assessment is important to support early identification of metabolic risk and sarcopenic obesity.